Designing Plant-Based Foods: Biopolymer Gelation for Enhanced Texture and Functionality - Luísa Ozorio; Aline Beatriz Soares Passerini; Ana Paula Corradi da Silva; Anna Rafaela Cavalcante Braga; Fabiana Perrechil (Foods)
Despite the wide variety of plant-based products, developing high-protein products with a desirable texture remains a key challenge for the food industry. Polysaccharide and plant-protein gels offer a cost-effective strategy for meeting the growing demands of vegan and vegetarian markets. This study aimed to develop mixed pea protein–polysaccharide gels with tailored textural properties for plant-based products. The gels were prepared using pea protein and different polysaccharides, including low-acyl gellan gum (GGLA), carrageenan (CA), pectin (PEC), and high-acyl gellan gum (GGHA), along with 60 mM NaCl or CaCl2. The dispersions were heated to 80 °C for 30 min under mechanical stirring, followed by a pH adjustment to 7.0 with NaOH (0.1 M). The samples were then analyzed via oscillatory temperature sweep rheometry, confocal microscopy, and uniaxial compression. Self-supporting and non-self-supporting gels were obtained from the various formulations, comprising pure polysaccharide and mixed gels with diverse textures for food applications. The developed gels show a strong potential for use in meat analogs, cheeses, cream cheeses, and sauces, offering the flexibility to fine-tune their mechanical and sensory properties based on the product requirements. Combining biopolymers enables customized texture and functionality, addressing critical gaps in plant-based food innovation.